Educational Strategies of Diabetes Group Medical Visits: A Review - Kirk, Julienne K.; Devoid, Hannah M.; Strickland, Carmen G. (Current Diabetes Reviews, 2018)
Background: Diabetes is a demanding disease that is growing in prevalence. Improved outcomes for patients with diabetes are highly dependent on self-management skills and the ability to make lifestyle changes. Innovative healthcare approaches are necessary to meet these specific patient needs. A group care medical visit (GMV) combines diabetes check-ups with diabetes education in a supportive and patient centered environment that promotes effective self-management. GMVs are associated with improved diabetes outcomes including hemoglobin A1C, weight, and self-efficacy; however details of the methods by which content is delivered to achieve these outcomes remain vague. Introduction: Improved GMV diabetes outcomes may be the result of specific processes used in group care models. We seek to describe educational strategies, content, and qualities of facilitators that contribute to successful outcomes associated with diabetes GMVs. Methods: A review of the literature was conducted focusing on diabetes GMVs, specifically the educational strategies implemented, topics discussed, and facilitator qualities that contribute to successful outcomes. Results: We identified 260 citations containing information about GMVs in patients with diabetes. A total of 7 citations met inclusion criteria and additional 5 were found through reference lists and relevant papers. Conclusion: Diabetes GMV educational topics comprise standard themes of disease process, medication, nutrition, and exercise. Several programs, however, target the development and realization of individualized patient goals, giving the patient more involvement in the session. Methods for facilitation may hold the key to successfully activating patients to reach meaningful behavior change goals. In addition to using expert clinical skills in diabetes care, effective facilitators provide support, and empower patients to take ownership of their diabetes. Rigorous evaluation of best practices for both the type and methods of delivering content in GMVs is lacking. Translational research to evaluate the relative effectiveness of educational strategies can be leveraged toward the successful scale and spread of this innovative primary care model.
Keywords: shared medical visit